Hydrogeological Earthquake Precursors: A Case Study From the Kamchatka Peninsula - Kopylova, Galina; Boldina, Svetlana (Frontiers in Earth Science, 2020)
The relevance of hydrogeological precursors (HGPs) study is justified by the need to obtain reliable information about the spatio-temporal manifestations and the relationships of HGPs with the parameters of subsequent earthquakes for seismic forecasting. In the review the data on repeated manifestations of HGPs before strong earthquakes obtained from long-term observations in five deep wells on the Kamchatka Peninsula (Far East of Russia) are presented. The analysis of the correlation of HGPs occurring in several wells is carried out in comparison with earthquake parameters characterizing both earthquake sources (magnitude, linear size of the source) and the impact of earthquakes in the area of wells (specific energy density in wave, intensity of shaking). It is shown that the manifestation of HGPs in several wells is observed before earthquakes with Мw=6.6–7.8 at epicentral distances up to the first hundreds of km to observation wells in the near and intermediate zones of the sources with the ratio of the epicentral distances and the source sizes no more than 1–5. A feature of our study was the use of certain types of HGPs in water-level changes for predictive assessments of the strong earthquakes in the Kamchatka Peninsula. The review presents precursors in water-level changes detected in real time and the corresponding earthquake forecasts, which were recognized as successful according to the conclusions of the expert council on earthquake prediction.